Patchy landscapes support more plant diversity and ecosystem services than wood grasslands in Mediterranean silvopastoral agroforestry systems. (November 2020) - Bagella, Simonetta; Caria, Maria Carmela; Seddaiu, Giovanna; Leites, Laura; Roggero, Pier Paolo
Abstract: Plant diversity and proxy indicators of ecosystem services were assessed for three structural components of Mediterranean silvopastoral agroforestry systems: WL = cork oak woodlands, WG = cork oak wood grasslands, and OG = open grasslands. Our study was conducted in a long-term observatory located in NE Sardinia, characterized by fragmented land ownership and land use, which generates a patchy landscape that is different from the extensively studied large scale Iberian dehesas and montados . Our research question was focused on assessing whether, a "patchy" land use scenario made of the combination of WL, WG and OG or a "specialized" scenario could provide more plant diversity and ecosystem services than a " dehesa type" scenario including only WG under the same overall tree cover. The results showed that γ and β diversity, species unique to a position, C stock, cork and acorn production, Hemicryptophytes cover, nectariferous species cover, decreased and pastoral value, excellent and good forage species and legume cover, increased along the WL➔WG➔OG land use gradient. Isolated trees in WG and clearings in WL highly contributed to achieving mainly high C stock and plant diversity respectively. The results also showed that the "specialized" scenario can support higher biodiversity and better ecosystem services than the " dehesa type" scenario, but the "patchy" scenario made of all three components proved to support the highest level of both biodiversity and ecosystem services in Mediterranean silvopastoral agroforestry systems. Highlights: Woodlands, open and wood grasslands are key components of silvopastoral systems. Biodiversity and C stock decreased with silvopastoral land use intensity. Pastoral value and in situ valuable germplasm increased with land use intensity. Clearings in cork oak woodlands enhanced C stock and plant diversity. A patchy landscape is ideal for enhancing plant diversity and ecosystem services.